Periodontal therapy mitigates inflammation via TNF-α reduction and improves glycolipid metabolism in diabetic patients: a cross-sectional cohort study - Guo, Yiman; Zhang, Xincheng; Yang, Aige; Guo, Yuqing; Dong, Shanshan; Wang, Lina; Zhang, Ning; Zhou, Huimin (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the effects of non-surgical periodontal therapy on systemic and local levels of tumor necrosis factor-alpha (TNF-α) and their relationship with glycolipid metabolism in patients with type 2 diabetes mellitus (T2DM) and periodontitis.MethodsIn this prospective cohort study, 234 patients with T2DM and periodontitis underwent standardized non-surgical periodontal therapy, including scaling and root planing, supplemented with systemic antibiotics. Clinical parameters (gingival bleeding index, periodontitis staging and grading), serum levels of TNF-α, HbA1c, leptin, adiponectin, resistin, free fatty acids (FFA), and levels of TNF-α, leptin, adiponectin, and resistin in gingival crevicular fluid (GCF) were assessed at baseline, 4 weeks, and 8 weeks post-treatment. Correlations were analyzed using Spearman’s rank correlation with false discovery rate correction.ResultsPeriodontal therapy resulted in significant improvements in all clinical periodontal parameters (P<0.01). Systemic and local GCF levels of TNF-α, leptin, resistin, and FFA demonstrated significant and progressive reductions, while adiponectin levels increased significantly at 4 and 8 weeks (P<0.01). HbA1c and FBG levels were also significantly improved by week 8 (P<0.01). TNF-α dynamics were strongly correlated with adipokine levels and clinical indices, with the most robust correlations observed within the GCF microenvironment.ConclusionSystematic periodontal therapy effectively reduces local and systemic inflammation, improves glycemic control, and ameliorates glycolipid metabolic disorders in patients with T2DM and periodontitis. The strong interrelationships observed, particularly within the GCF, underscore the potential role of TNF-α as a key mediator in the mouth-systemic metabolic interplay.